Relasi Islam-Kristen: Studi Kasus di Desa Tegalombo, Pati, Jawa Tengah - Ghufron, Ghufron (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2020)
This paper wants to build an alternative model for caring for inter-religious harmony. The model can be found through the cultural mechanism that occurs in Islamic-Christian relations in Tegalombo Village, Pati, Central Java. The foundation of harmony between the two religions rests on the sustainability of three harmony models, namely: First, interfaith prayer in the celebration of family or village level; Second, culture visits each other during feast days, when someone is sick, and the inter-food sharing as a form of connecting harmony. Third, practical model dialogue in the Selapanan forum that brings together two religious groups in order to discuss various issues of security and social development. On the other hand, the relationship between the two also triggered a tension triggered by the contestation over the dominance of religious broadcasting with certain techniques such as recitation (Islam) and Revival Service (Christian).